2004
DOI: 10.1002/imhj.20006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of the adult attachment interview in parent–infant psychotherapy

Abstract: This article provides an illustration of how the use of the Adult Attachment Interview (AAI; George, can be extended beyond the research arena to its use as a clinical instrument in parent-infant psychotherapy. The article is based on the ongoing work of the Parent-Infant Project team at the Anna Freud Centre, London, where psychoanalytically trained therapists routinely administer the AAI early in the therapeutic process. In the first part of the article, we introduce the thinking behind the use of the AAI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
2
17
0
1
Order By: Relevance
“…Not infrequently in this clinical sample a switch in ego state signals the narration of a horrifying history of abuse suffered at the hand of an attachment figure that is not accessible to the preceding ego state. Steele and Steele (2003), while reporting the preliminary findings of their study, call attention to an observation that can be confirmed by many clinicians dealing with the traumatic memories of adult survivors of child abuse: "while psychic pain certainly accompanies the recall of the abuse per se, this pales in comparison to the much greater pain that accompanies the recall of being betrayed by trusted caregivers and siblings" (Steele & Steele, 2003, p. 116-117). That is, the memory of an attachment figure who fails to protect the child from the abuse perpetrated by another member of the family may be more painful than the memory of the abuse per se.…”
Section: Trauma and Dissociation In Research Findings Based On The Admentioning
confidence: 88%
See 3 more Smart Citations
“…Not infrequently in this clinical sample a switch in ego state signals the narration of a horrifying history of abuse suffered at the hand of an attachment figure that is not accessible to the preceding ego state. Steele and Steele (2003), while reporting the preliminary findings of their study, call attention to an observation that can be confirmed by many clinicians dealing with the traumatic memories of adult survivors of child abuse: "while psychic pain certainly accompanies the recall of the abuse per se, this pales in comparison to the much greater pain that accompanies the recall of being betrayed by trusted caregivers and siblings" (Steele & Steele, 2003, p. 116-117). That is, the memory of an attachment figure who fails to protect the child from the abuse perpetrated by another member of the family may be more painful than the memory of the abuse per se.…”
Section: Trauma and Dissociation In Research Findings Based On The Admentioning
confidence: 88%
“…Interestingly, most "cannot classify" interviews are also rated high for unresolved traumas and/or losses (Hesse, 1996;Steele & Steele, 2003). This is a further hint that "cannot classify" interviews may indicate the presence of a type of sub-clinical post-traumatic dissociative process, characterized both by poor metacognitive monitoring and by autobiographical memories that are split as to the meaning attributed to events.…”
Section: Trauma and Dissociation In Research Findings Based On The Admentioning
confidence: 97%
See 2 more Smart Citations
“…De plus, des recherches et des théorisations récentes (Barach, 1991 ;Blizard 1997Blizard , 2001Blizard , 2003Carlson, 1998 ;Liotti, 1992Liotti, , 1995Liotti, , 1999Liotti, , 2004Liotti, , 2006Lyons-Ruth, 2003, 2006Ogawa, Sroufe, Weinfeld, Carlson et Egeland, 1997 ;Pasquini, Liotti et The Italian Group for the Study of Dissociation, 2002 ;Steele et Steele, 2003) démontrent que l'attachement désorganisé (AD) jouerait un rôle tout aussi important, sinon plus important, que le trauma dans le développement de la dissociation pathologique et du TDI. L'attachement se forme lors d'interactions où un enfant cherche du réconfort auprès d'une figure affective importante.…”
Section: Le Trouble Dissociatif De L'identité (Tdi)unclassified